Comparison of Biochemical and Pathological Parameters and Parenteral Nutrition of ICU Patients Under Supervision of Dietitians and Surgeons - Behrad Nasab, Mojgan; Akbari, Mohammad Esmail; Rastgoo, Samira; Gholami, Somayeh; Hajipour, Azadeh; Majidi, Nazanin; Gholamalizadeh, Maryam; Mirzaei Dahka, Samaneh; Doaei, Saied; Goodarzi, Mark O. (Frontiers in Nutrition, 2021)
Background: Nutrient imbalance can frequently occur in patients with indications for total parenteral nutrition (TPN) after gastrointestinal surgery. This study aimed to compare the recommendations of a surgeon to those of a dietitian in the field of parenteral nutrition. Methods: This study was performed on 256 patients undergoing gastrointestinal surgery who received TPN, which included 120 patients who received TPN based on recommendations of the surgeons and 136 patients who were referred to receive TPN under the supervision of a dietitian in Razi Hospital in Rasht, Iran. Data on TPN and clinical outcomes of the patients were collected. Results: Patients under the supervision of dietitians received higher vitamin B complex and lipids and lower vitamin A and vitamin E than the surgeon-supervised patients (all P<0.001). In the group receiving TPN under the supervision of a surgeon, the level of blood glucose (207 vs 182, P<0.01), sodium (138 vs 136, P=0.01), potassium (3.97 vs 3.53, P<0.01), and white blood cell count (9.83 vs 9.28, P<0.01) increased significantly at the end of the TPN compared to baseline. In the group receiving TPN under the supervision of a dietician, the level of serum Cr (1.23 vs 1.32, P=0.04), Mg (2.07 vs 1.84, P<0.01), and pH (7.45 vs 7.5, P=0.03) significantly improved after receiving parenteral nutrition compared to baseline. Conclusion: The amounts of nutrients recommended for TPN by the surgeon and dietitian were different. Implementation of dietitian recommendations in critically ill patients under TPN can improve patients' clinical parameters.